Studies on the Feeding Relationships of Leeches (Annelida: Hirudinea) As Natural Associates of Mollusks - Donald J. Klemm (Hello World!, 1975)
This study was designed to determine the degree of host-specificity of leeches of the family Glossiphoniidae, genera Helobdella, Glossiphonia, and Marvinaeyeria in their relation to freshwater mollusks in southern Michigan. Four families and seven species of operculates, three families and nineteen species of pulmonates, and one family of three species of sphaeriacean clams were examined for leeches over a two-year period. lnformation is also provided on other parasites and symbionts found on mollusks infested with particular species of leeches. Leeches infesting mollusks within several different habitats, such as lakes, ponds, woodland pools, creeks, and roadside ditches are compared.